Studies on mononuclear chelates derived from substituted Schiff-base ligands (part 7): synthesis and characterization of a new naphthyliden-p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Canpolat, E; Kaya, M (Taylor & Francis Ltd, 2005)
In this study, the new ligand, naphthyliden-p-aminoacetophenoneoxime (LH) was synthesized starting from p-aminoacetophenoneoxime and 2-hydroxy-1-naphthaldehyde. Mononuclear complexes with a metal ligand ratio of 1 : 2 have been prepared with Co(II), Ni(II), Cu(II) and Zn(II) salts. Their structures have been elucidated on the basis of elemental analyses, IR, H-1- and C-13-NMR spectra, UV-Vis spectra, magnetic susceptibility measurements, molar conductivity and thermogravimetric analyses (TGA).
Keywords: Schiff bases; transition metal complexes